2008
DOI: 10.1099/mic.0.2007/012195-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Aggregatibacter actinomycetemcomitans leukotoxin expression by IS1301 and orfA

Abstract: Most Aggregatibacter actinomycetemcomitans strains express relatively low levels of leukotoxin, encoded by the orfA-ltxCABD operon. However, several strains isolated from patients with localized aggressive periodontitis are hyperleukotoxic and transcribe the ltx operon at high levels. These strains possess a copy of IS1301 in the ltx promoter and previous studies have suggested that the presence of the insertion sequence increases ltx transcription by uncoupling a cis-acting negative regulator of ltx expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The promoter region in these strains was 1926 bp in length and contained a DNA transposable element (IS1301) that was required for high leukotoxicity. More recently, Schaeffer et al (2008) characterized the mechanism that leads to overproduction of LtxA in these strains. They reported that both the transposase promoter and a protein encoded by an open reading frame just upstream of ltxC (OrfA) are required for maximal transcriptional activity of the operon.…”
Section: The Ltx Promotermentioning
confidence: 99%
“…The promoter region in these strains was 1926 bp in length and contained a DNA transposable element (IS1301) that was required for high leukotoxicity. More recently, Schaeffer et al (2008) characterized the mechanism that leads to overproduction of LtxA in these strains. They reported that both the transposase promoter and a protein encoded by an open reading frame just upstream of ltxC (OrfA) are required for maximal transcriptional activity of the operon.…”
Section: The Ltx Promotermentioning
confidence: 99%
“…AI-2 produced by A. actinomycetemcomitans regulates expression of virulence factors, biofilm formation, and iron uptake and also influences the planktonic growth of the organism under conditions of iron limitation (13,38,41). A. actinomycetemcomitans possesses two periplasmic AI-2 receptors, LsrB and RbsB, both of which are linked to ABC transporters (19,40), suggesting that A. actinomycetemcomitans may import AI-2.…”
mentioning
confidence: 99%
“…This organism expresses LuxS and secretes autoinducer 2 (AI-2), and AI-2-dependent quorum sensing has been shown to regulate the expression of virulence factors, iron acquisition systems, and biofilm formation (17)(18)(19)(20). The complex regulatory network involved in A. actinomycetemcomitans biofilm growth and the role of quorum sensing in this process have begun to be explored in recent years.…”
mentioning
confidence: 99%